High-yield webinar engagement strategies and teacher candidate professional learning - Cosier, Meghan; Morgan, Sara; Sandoval Gomez, Audri (Frontiers in Education, 2022)
In response to the COVID-19 school closures in both K-12 and higher education, a group of education partners in the U.S. collaborated to offer a statewide webinar series, 12 webinars in total, to support preservice teachers as they worked to complete their clinical hour requirements. The webinars and extension activities provided via Padlets covered topics associated with best practices and related to credential requirements such as applying universal design for learning and differentiating instruction. This study explored the perceptions of 248 preservice teachers regarding the virtual professional learning format and extension activities, as well as what professional learning they felt they needed in the future as they began their first year teaching during COVID-19. Findings suggest preservice teachers were receptive to learning through the structured webinar platform and found extension activities helpful in applying content. Their knowledge, sense of preparedness, and application of the topics and strategies presented increased, and the topics were relevant and supported the required practicum hours and future teaching practice.